2019
DOI: 10.4236/tel.2019.94075
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Impact of Quality, Openness and Reputation of Massive Open Online Courses MOOCs on an Individual’s Satisfaction and Performance

Abstract: Purpose of the Study: The research objective is to explore the important characteristics of MOOCs that impact an individual user's satisfaction and his/her performance. There is a paucity of understanding if the MOOCs affect the individual performance and what are the various characteristics of MOOCs that determine the same. Therefore, it is important to understand the success of MOOC platform from the user's performance perspective. Data/Methodology: Structural equation modelling was used to analyze the data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…This result is agreeable with that of Chen et al, (2018) and Alraimi et al, (2015). The second MOOC feature, perceived reputation also demonstrated no significant impact on satisfaction which is consistent with Khurana et al, (2019). However, there are very limited studies to confirm the relationship between perceived openness and perceived reputation on satisfaction.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This result is agreeable with that of Chen et al, (2018) and Alraimi et al, (2015). The second MOOC feature, perceived reputation also demonstrated no significant impact on satisfaction which is consistent with Khurana et al, (2019). However, there are very limited studies to confirm the relationship between perceived openness and perceived reputation on satisfaction.…”
Section: Discussionsupporting
confidence: 86%
“…Openness will provide easy access to course resources which will enhance satisfaction (Chen et al, 2018;Choi et al, 2019) as well as perceived usefulness (Choi et al, 2019). Even Khurana et al, (2019) confirmed the positive influence of openness on satisfaction. Therefore, we hypothesize that, H6: Perceived openness has a positive impact on satisfaction.…”
Section: Perceived Opennessmentioning
confidence: 86%
“…An open education community such as MOOC has concentrated over time on greater openness, enabling the community to provide visible and accessible educational materials through free access, greater choice, and flexibility [40,41]. Many students are interested in MOOCs due to their widespread and open nature compared to receiving certificates of any kind or academic credit [43]. Mohapatra and Mohanty [44] further revealed that behavioural intention to use MOOCs is significantly and positively affected by affordability.…”
Section: Openness (Cast Advantage)mentioning
confidence: 99%
“…In this light, an effective MOOC can draw more participation [48] because students' and lecturers' participation is dependent on their beliefs and their views on MOOCs [9]. The reputation of educational institutions is alluring to students because it serves as the perceived excellence of an institution which influences the choices of future students to attend the school [43,49]. In short, the initial assessment of the course's reputation or university can, therefore, influence the student's decision to withdraw [48].…”
Section: Reputationmentioning
confidence: 99%